Carbenoid-mediated nucleophilic “hydrolysis” of 2-(dichloromethylidene)-1,1,3,3-tetramethylindane with DMSO participation, affording access to one-sidedly overcrowded ketone and bromoalkene descendants§ - Knorr, Rudolf; Menke, Thomas; Freudenreich, Johannes; Pires, Claudio (Beilstein Journal of Organic Chemistry, 2014)
2-(Dichloromethylidene)-1,1,3,3-tetramethylindane was “hydrolyzed” by solid KOH in DMSO as the solvent at ≥100 °C through an initial chlorine particle transfer to give a Cl,K-carbenoid. This short-lived intermediate disclosed its occurrence through a reversible proton transfer which competed with an oxygen transfer from DMSO that created dimethyl sulfide. The presumably resultant transitory ketene incorporated KOH to afford the potassium salt of 1,1,3,3-tetramethylindan-2-carboxylic acid (the product of a formal hydrolysis). The lithium salt of this key acid is able to acylate aryllithium compounds, furnishing one-sidedly overcrowded ketones along with the corresponding tertiary alcohols. The latter side-products (ca. 10%) were formed against a substantially increasing repulsive resistance, as testified through the diminished rotational mobility of their aryl groups. As a less troublesome further side-product, the dianion of the above key acid was recognized through carboxylation which afforded 1,1,3,3-tetramethylindan-2,2-dicarboxylic acid. Brominative deoxygenation of the ketones furnished two one-sidedly overcrowded bromoalkenes. Some presently relevant properties of the above Cl,K-carbenoid are provided in .
Keywords: brominative deoxygenation; carbenoid; DMSO; nucleophilic vinylic substitution; steric hindrance